2013
DOI: 10.1128/jvi.00546-13
|View full text |Cite
|
Sign up to set email alerts
|

The B-Cell-Specific Transcription Factor and Master Regulator Pax5 Promotes Epstein-Barr Virus Latency by Negatively Regulating the Viral Immediate Early Protein BZLF1

Abstract: The latent-to-lytic switch of Epstein-Barr virus (EBV) is mediated by the immediate early protein BZLF1 (Z).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 73 publications
0
36
0
Order By: Relevance
“…Given that the PAX5 and Oct-2 proteins inhibit Z activity (55,56) and that PAX5 represses synthesis of XBP-1 in lymphoid cells (57), one might expect that addition of BLIMP1 would induce EBV lytic gene expression in some EBV ϩ B-cell lines under some conditions; this hypothesis has been validated (58). Other investigators reported that while expression of EBV Z protein was restricted to BLIMP1-positive epithelial cells in oral hairy leukoplakia (OHL) tissue samples, this relationship did not hold in IM tonsillar B cells, suggesting that BLIMP1 may be necessary for induction of EBV lytic gene expression during differentiation of epithelial but not B cells (59).…”
Section: Importancementioning
confidence: 99%
“…Given that the PAX5 and Oct-2 proteins inhibit Z activity (55,56) and that PAX5 represses synthesis of XBP-1 in lymphoid cells (57), one might expect that addition of BLIMP1 would induce EBV lytic gene expression in some EBV ϩ B-cell lines under some conditions; this hypothesis has been validated (58). Other investigators reported that while expression of EBV Z protein was restricted to BLIMP1-positive epithelial cells in oral hairy leukoplakia (OHL) tissue samples, this relationship did not hold in IM tonsillar B cells, suggesting that BLIMP1 may be necessary for induction of EBV lytic gene expression during differentiation of epithelial but not B cells (59).…”
Section: Importancementioning
confidence: 99%
“…17 In addition, important B-cell transcription factors repressing plasma cell differentiation have been shown to repress also EBV replication. 36,37 Curiously most of post-transplant lymphoproliferative disorders exhibit plasma cell differentiation suggesting a connection between these two events in transplant recipients. It is of interest that, as in other aggressive lymphomas, XBP1 activation is related to aggressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…4C). The levels of Oct-2, Pax-5, ZEB1, and YY1, negative regulators of Z's activities or BZLF1 expression (14,15,62,75), also declined. Unexpectedly, the level of Ikaros RNA did not decline significantly.…”
Section: Ikaros Contributes To Maintenance Of Ebv Latency In B Cellsmentioning
confidence: 99%
“…EBV establishes long-term latency in B cells, undergoing reactivation when they differentiate into plasma cells (2). Some Bcell-specific factors (e.g., Oct-2 and Pax-5) promote EBV latency (14,15), while some plasma-cell-specific factors (e.g., XBP-1s and BLIMP-1) promote EBV lytic replication (6,7,70,71). To further understand how Ikaros contributes to EBV latency, we examined the effect of changing its level on the expression of some cellular factors known to play key roles in regulating EBV's latent-lytic switch or B-cell differentiation into plasma cells.…”
Section: Ikaros Contributes To Maintenance Of Ebv Latency In B Cellsmentioning
confidence: 99%
See 1 more Smart Citation